Cryptobrachytone C from Cryptocarya pulchrinervia (Kosterm) Leaves on Proliferation, Apoptosis, Migration and Clonogenicity of MCF-7 and T47D Cell Lines - Jujun Ratnasari; Marselina Irasonia Tan; Rizkita Rachmi Esyanti; Lia Dewi Juliawaty (Tropical Life Sciences Research, 2023)
Cryptocarya pulchrinervia is an Indonesian indigenous plant that grows in Sumatra, Kalimantan and Papua. One of the new compounds extracted from this plant was cryptobrachytone C, which was known to be cytotoxic against cancer cells of Murine leukemia P388 with IC50 10.52 ?M. In this study, the cytotoxicity and anticancer properties of cryptobrachytone C on proliferation, apoptosis, migration and clone formation of MCF-7 and T47D breast cancer cell lines were examined, which had not previously been done before. The cytotoxicity of the compound was measured using an MTT (3- (4,5-dimethylthiazol-2- yl) -2,5-di-phenyl-tetrazolium bromide) assay. The cell proliferation was measured using a BrdU assay, and the cell apoptosis was measured using annexin-V FITC, while the cell migration was measured using a transwell filter. The cytotoxic test result demonstrated that cryptobrachytone C was cytotoxic against MCF-7 cells with IC50 12.94 ± 0.32 ?M but not against T47D cells with IC50 65.33 ± 2.33 ?M nor against normal MRC-5 cells with IC50 122.57 ± 19.84 ?M. The cell proliferation assay showed that cryptobrachytone C at IC50 concentration had antiproliferative properties against MCF-7 cancer cell lines (p < 0.05) but did not significantly reduce T47D cell proliferation (p < 0.07). Although the results of the cell apoptosis test showed that cryptobrachytone C could induce the apoptosis of the MCF-7 and T47D cells, it was insignificant (p > 0.05). The cell migration test showed that cryptobrachytone at IC50 concentrations could inhibit the migration of the MCF-7 and T47D cells. The clonogenic test showed that cryptobrachytone C at IC50 concentration can induce the inhibition of the formation of MCF-7 and T47D cell colonies. The cryptobrachytone C anti-cancer character was more significant on the MCF-7 cell line compared to the T47D. This study showed that cryptobrachytone C was cytotoxic and had potential as an anti-cancer compound against MCF-7 and T47D breast cancer cell lines.